THE EFFECT OF TEAMS GAMES TOURNAMENT (TGT) LEARNING MODEL WITH MONOPOLY GAME MEDIA ON MATHEMATICS LOGIC INTELLIGENCE - Pangesti, Nia; Mardiana, Tria; Rasidi, Rasidi (Prosiding University Research Colloquium, 2021)
This study aims to determine the effect of of Teams Games Tournament (TGT) learning model with monopoly game media on mathematical logic intelligence in grade V Student of SD Negeri Keji 2, Muntilan District, Muntilan Regency. This type of research is pre-experimental with one group pretest-posttest design. The sample taken in class V SD Negeri Keji 2 with a total of 18 students. The sampling technique used was saturated sampling. Test data analysis using prerequisite test or normality test and hypothesis testing. Data retrieval through multiple choice test questions was then analyzed using the Wilcoxon test in the SPSS 23.00 program for windows. The results showed that the Teams Games Tournamnet learning model with monopoly game media had an effect on students mathematical logis intelligence. This is evidenced by the results of the analysis of the Wilcoxon signed rank test analysis of-3.732 with Asymp. Sig 2 tailed is 0,000 < 0,005. So that Z output < mean rank or 3,732 < 9,50 Ha is accepted and Ho is rejected. The data identify the data points are smaller than the average. Based on the result of the analysis the and discussion, there are differences in the in the results of the average value, namely the initial measurement (pretest) of 41,3 and the final measurement (posttest) of 73,1. From the results of the study it can be concluded that the Teams Games Tournament (TGT) learning model with monopoly game media has an effect on students mathematical logic intelligence.